Usaha Kreatif Membuat Jajanan Berbahan Singkong Pada Masyarakat Kelurahan Gemah, Kecamatan Pedurungan, Kota Semarang - Imam Gozali; Ratnawati Dwi Putranti (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This service was held in Kel. Gemah, Kec. Pedurungan, Semarang City. The aim is to create non-formal business opportunities that non-working housewives can do. Techniques for implementing community service using theoretical and practical learning methods. The target of this service is 20 housewives. The results to be achieved are 1) the participants understand the meaning of creative business and are able to run a home business, especially making snacks from cassava. 2) Not only that, but also able to market their own products. Community Service as one of the Tri Dharma of Higher Education will be carried out in a sustainable manner.